2020
DOI: 10.5187/jast.2020.62.3.409
|View full text |Cite
|
Sign up to set email alerts
|

The effects of breed and gender on meat quality of Duroc, Pietrain, and their crossbred

Abstract: This study evaluated the effects of breed and gender in Duroc (D), Pietrain (P), and crossbred (DP) pigs. Loin samples were collected from D (n = 79), P (n = 42), and DP (n = 45) pigs. Intramuscular fat content was significantly lower in P (p < 0.001), and pH was lowest in DP pigs (p < 0.001). Gilts had higher intramuscular fat (IMF) and pH values than did castrated males (p < 0.05). Water-holding capacity was lower in DP pigs than that in D and P pigs (p < 0.001). Shear force in DP pigs was higher than that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
4
16
0
Order By: Relevance
“…As expected, a significant influence of Duroc genotype on IMF content was found, which has long been considered one of the breed traits of Duroc [ 38 ] and has been confirmed by many authors [ 2 , 9 , 37 , 39 , 40 ]. Apart from the possible influence of Duroc genotype, the high content of IMF in (LWxL)xD of raw ham is certainly a consequence of the prolonged fattening [ 41 ] and the much higher final weights of the pigs [ 42 ].…”
Section: Resultssupporting
confidence: 77%
“…As expected, a significant influence of Duroc genotype on IMF content was found, which has long been considered one of the breed traits of Duroc [ 38 ] and has been confirmed by many authors [ 2 , 9 , 37 , 39 , 40 ]. Apart from the possible influence of Duroc genotype, the high content of IMF in (LWxL)xD of raw ham is certainly a consequence of the prolonged fattening [ 41 ] and the much higher final weights of the pigs [ 42 ].…”
Section: Resultssupporting
confidence: 77%
“…This fact may be an indication that DUR pigs may be more sensitive to ractopamine supplementation in relation to meat color. In addition, previous studies indicate that meat color is influenced by breed (Li et al, 2013;Zhang et al, 2018;Kim et al, 2020) which could explain the differences observed in the present study.…”
Section: Discussionsupporting
confidence: 49%
“…In addition to pH, Table 1 shows the results for the color of the breast and thigh of the spent hen and broiler. Color is an important factor because it has a major, direct impact on consumers’ purchasing rates and preferences [ 21 ]. Lightness was significantly higher in BT than in SB and BB, which can be explained by the higher accumulation of the blood pigment myoglobin in thigh meat than in breast meat, which has a low exercise capacity.…”
Section: Resultsmentioning
confidence: 99%